Penetração e alterações teciduais do laser de alta intensidade em tecidos moles e duros da cavidade bucal - Aecio Abner Campos Pinto Junior (2018)
The treatment of several odontogenic cysts and tumors is commonly associated with an adjuvant therapy, aiming for lower recurrence rates and a better prognosis. There are some related methods however, to our knowledge, the high intensity lasertherapy was not studied fully on this matter. LASER is an acronym for Light Amplification by Stimulated Emission of Radiation. The use of laser in Dentistry is being recognized in the literature and become a useful therapeutic tool among professionals. This technology has evolved considerably over the past few years and nowadays a wide variety of laser types of equipment is being used for several purposes. The diode laser is one of this emerging tool e has great applicability in Dentistry. The literature about this type of laser is wide but there is no consensus about its penetration in different tissues, as well as the effects caused by laser-tissue interaction, are not fully understood. The aim of this study was to evaluate the laser effects on tissues and its penetration in both soft and hard tissues of New Zealand rabbits, in order to investigate if the results could contribute for using this therapy on mouth lesions treatment. It was realized an experiment with 18 animals ex vivo. After the euthanasia, the samples of oral mucosa and mandibular bone, bilaterally, were acquired. The tissues were marked in areas for receiving the laser therapy in two different periods (G1 and G2). The equipment was set in 4.5W. It was obtained 08 samples of each irradiated tissue for histological evaluation. Descriptive analysis revealed that soft tissues of G2 (higher energy of laser) presented bigger tissue damage. The depth of laser penetration on the bone tissue was analyzed and resulted in measurements of 13,52 µm (G1) and 10,32 µm (G2). Statistical analysis of bone samples did not reveal a significant difference (p = 0,123) between G1 and G2 regarding laser penetration on evaluated tissues.